PEMBINAAN PERILAKU HIDUP SEHAT SISWA SISWI SEKOLAH DI MOJOKERTO. - Eka Diah Kartiningrum (Jurnal Pengabdian Masyarakat, 2021)
The second session of community service activities carried out from February to July 2021 is part of the effort to foster healthy living behavior for students in the Mojokerto area which takes the topic of the implications of wearing masks, keeping a distance and washing hands. This activity was carried out in groups of kindergarten students, TPQ students and high school students. Coaching for TK and TPQ students is carried out directly (offline) by dividing students into several groups to prevent crowds. Meanwhile, for high school students, it is done online using the Google Meet facility. The results of the coaching showed an increase in the knowledge of students and students after receiving coaching. Good synergy and cooperation between health workers and the community will create stable healthy lifestyles and comply with health protocols so that they are able to control the Covid 19 pandemic in Indonesia.